2014
DOI: 10.1007/s10482-014-0362-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of chitosan against wine-related microorganisms

Abstract: The antimicrobial action of chitosan against wine related microorganisms, including Lactobacillus plantarum, Saccharomyces cerevisiae, Oeonococcus oeni, Lactobacillus hilgardii, Brettanomyces bruxellensis, Hanseniaspora uvarum and Zygosaccharomyces bailii was examined in laboratory media. In order to assess the potential applicability of chitosan as a microbial control agent for wine, the effect of chitosan, applied individually and/or in combination with sulphur dioxide (SO2), on the growth of microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Certain forms of chitosan, a natural polymer derived from chitin, exhibit antimicrobial properties. Chitosan is well known for its antimicrobial properties against yeast, bacteria, and fungi [57,58], and a preparation extracted from a fungal source has been used to neutralize contamination by Brettanomyces bruxellensis [59]. More recently, Chitosanglucan formulation has been released to inhibit wine lactic acid bacteria and delay or inhibit malolactic fermentation.…”
Section: Residual Lysozyme Activity and Chitosan Formulationmentioning
confidence: 99%
“…Certain forms of chitosan, a natural polymer derived from chitin, exhibit antimicrobial properties. Chitosan is well known for its antimicrobial properties against yeast, bacteria, and fungi [57,58], and a preparation extracted from a fungal source has been used to neutralize contamination by Brettanomyces bruxellensis [59]. More recently, Chitosanglucan formulation has been released to inhibit wine lactic acid bacteria and delay or inhibit malolactic fermentation.…”
Section: Residual Lysozyme Activity and Chitosan Formulationmentioning
confidence: 99%
“…Moreover, due to the increasing interest in more organic wines, there is a tendency in the regulations for limiting the use of SO 2 , which have led to the search for alternative compounds to replace it [58]. Among these compounds there is chitosan, whose applicability as a microbial control agent against wine related microorganisms was recently studied [59]. The authors found that chitosan was able to inhibit the growth of the non-Saccharomyces yeasts Hanseniaspora uvarum, ZygoSaccharomyces bailii and Brettanomyces bruxellensis with Minimum Inhibitory Concentration (MIC) values of 0.4, 0.4, and 0.2 g L −1 , respectively.…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
“…Organic wine processing may be more challenging than that of conventional wine, especially under regulations prohibiting SO 2 . A number of compounds have been tested in order to replace SO 2 in wine, such as wine bacteriocins, chitosan and lysozyme (Díez et al, 2012;Bagder Elmaci et al, 2015;Ancìn-Azpilicueta et al, 2016), and several physical methods have been tested, including pulsed electric fields and high hydrostatic pressure (Santos et al, 2013). However, none of these practices provided a real replacement for SO 2 , or its use is not allowed in organic wine production (Guerrero & Cantos-Villar, 2015).…”
Section: Product Innovationmentioning
confidence: 99%